On the measure of sea ice area from sea ice concentration data sets - BOCCOLARI, Mauro; Parmiggiani, Flavio (SPIE Proceedings, Remote Sensing of the Ocean, Sea Ice, Coastal Waters, and Large Water Regions 2015, 2015)
The measure of sea ice surface variability provides a fundamental information on the climatology of the Arctic region. Sea ice extension is conventionally measured by two parameters, i.e. Sea Ice Extent (SIE) and Sea Ice Area (SIA), both parameters being derived from Sea Ice Concentration (SIC) data sets. In this work a new parameter (CSIA) is introduced, which takes into account only the compact sea-ice, which is defined as the sea-ice having concentration at least equal the 70%. Aim of this study is to compare the performances of the two parameters, SIA and CSIA, in analyzing the trends of three monthly time-series of the whole Arctic region. The SIC data set used in this study was produced by the Institute of Environmental Physics of the University of Bremen and covers the period January 2003 - December 2014, i.e. the period in which the data set is built using the new AMSR passive microwave sensor.